Tour Guide Styles and Penal History Museums in Canada. (15th October 2015) - Ferguson, Matthew; Walby, Kevin; Piché, Justin
Abstract: Although the existing penal tourism literature examines displays at penal heritage sites, little research has explored the work of tour guides within them. Drawing from interviews and observations, this article assesses the styles of tour guides working at penal history museums in Canada. We situate carceral guides' styles along a continuum encompassing those who claim to convey historical facts as well as ones who explicitly engage in staging and performance, which are primarily responsive to penal tourists' expectations for fun and entertainment. In the discussion and conclusion, we address the practical implications of this assessment of guide styles. Copyright © 2015 John Wiley & Sons, Ltd.